The Modern Service Strategies to Create a Competitive Advantage of Travel Agents in the Mekong Provinces in the Northeastern Region - Patcharachotsuthi, Paphawin (Journal of Business, Innovation and Sustainability (JBIS), 2022)
This research aimed to 1) study the factor analysis of modern service strategies to create a competitive advantage of travel agents in Mekong provinces in the Northeastern region and 2) examine the structural equation modelling of modern service strategies to create a competitive advantage of travel agent in Mekong provinces in the Northeastern Region. The data were collected by questionnaires. The samples were travel agent entrepreneurs in Nong Kai, Buengkan and Nakhon Phanom amount 113 entrepreneurs. The research instrument was factor analysis and orthogonal rotation by varimax method to study confirmatory factors by maximum likelihood. The results of the test to examine the accuracy of the model through KMO was .784, and Bartlett’s Test of Sphericity showed a significant value of .000, which means the variables were related to each other and can be used to analyze with seven factors, including 1) building a service image, 2) improving service through innovation, 3)focusing on specific market segments to response customers, 4) cost, 5) public relations, 6) service management, and 7) creative innovation. The result for the confirmatory factor analysis was conformed to the empirical data and accurate according to the model structure by considering ꭓ2 =566.273, dƒ = 213, ꭓ2/dƒ= 2.6585, CFI=0.986, TLI= 0.957, SRMR=0.040, RMSEA= 0.04.